USOS MIDIÁTICOS DO CORPO EM O TEMPO E O VENTO: O CASO ANA TERRA - Brito, Marcia Elena de (2016)
This paper proposes a comparative study of the character Ana Terra in the novel O Tempo e o Vento (1947) by Erico Verissimo and its homonymous adaptations for audiovisual in the miniseries format (1985) directed by Paulo José, and film (2013) by Jayme Monjardín. The objective was to verify the aesthetic and narrative transformations that the body of Ana Terra character suffered when transposed to those medias. Therefor, it was necessary to return to the journey of the character in the literary work, and from that point discuss how it was interpreted in the medias . We used as theoretical framework authors who talk about the dialogue of literature with other arts and also on the mediatic culture, such as: Regina Zilberman, Douglas Kellner and Claus Cluver. The methodology used was based primarily on review of available literature comparing it to the media. We seek, therefore, the primary sources (the books that make up the trilogy, specifically the first volume, O Continentein which is the chapter of the character Ana Terra). At the same time, we propose a comparative study of three different types of media (book, TV and Cinema).It was sought, therefore, to discuss how the transposition of a major character of Brazilian literature for television and then for film ocurred. We conclude that although departing from the same point (the literary work) the adaptations are different and unique works, and fit each in its own context, and that the transformations in character Ana Terra in those medias were necessary, taking note that each adaptation was produced during distinct periods, with different looks and different audiences.